Challenge with a Personal Cascade Impactor Sampler in a Silicon Metal Smelter - Balázs Berlinger; Torunn K. Ervik; Konrad Kandler; Bente Ulvestad; Nathalie Benker; Dag G. Ellingsen; Merete D. Bugge (Aerosol and Air Quality Research)
Abstract Cascade impactors are useful tools in the measurement of particle size mass distribution of workplace aerosols. The application of cascade impactors, however, is sometimes challenging. Personal aerosol samples were collected by Sioutas cascade impactors and respirable cyclones in parallel in a silicon (Si) metal smelter to investigate the different particulate matter (PM) fractions. In a second campaign, nine new air samples were collected with the Sioutas personal cascade impactors using stationary sampling. It was found that wall deposition was substantial in the upper stages of the Sioutas cascade impactors, which meant that quite often more PM was deposited on the inner walls of the impactor than on the filter substrates. At the same time, wall deposition did most probably not affect the collection of the finest particles (< 0.25 µm). Besides wall deposition of the particles, the effect of high PM concentration on the impactor performance, particle bouncing and blow off, high particle mass loading and impact fragmentation of the particle agglomerates were considered for explaining the malfunctioning of the Sioutas impactors in the Si metal smelter. Furthermore, concentrations of the finest PM fraction (< 0.25 µm) and respirable fraction both collected by personal sampling are reported and discussed in the paper.